Microsoft 70-466 : implementing data models and reports with Microsoft SQL Server 2012 - Dye, David; Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"This course is specifically for participants to gain the knowledge and skills for making the appropriate job role decisions around implementing data models and reports with Microsoft SQL Server 2012. This course is designed for BI Developers who most-likely focus on hands-on work creating the BI solution including implementing multi-dimensional data models, implementing and maintaining OLAP cubes, and creating information displays used in business decision making."--Resource description page.
Presenter, David Dye.
Title and publication information from resource description page (Safari, viewed June 14, 2017).
Keywords: SQL server -- Examinations -- Study guides; Database management -- Examinations -- Study guides; Electronic data processing personnel -- Certification -- Study guides; Client/server computing -- Examinations -- Study guides; OLAP technology; Electronic books